DOING GYMNASTICS TOGETHER WITH ELDERLY in GAMPONG KEURAMAT, KUTA ALAM DISTRICT, BANDA ACEH - Miftahul Jannah; Ira Dama Yanti; Manovri Yeni (Universitas Muhammadiyah Aceh, 2021)
The Elderly are individuals who are over 60 years old. Usually, at this age the ability and endurance of the individual's body decrease and coupled with the presence of various degenerative diseases that will appear, such as rheumatism, heart disease, hypertension, osteoporosis and diabetes mellitus. Based on data from the Central Statistics Agency (BPS) Banda Aceh on June 19, 2020, the total of elderly population in Banda Aceh is 13.245 people (6.576 men and 6.669 women), namely 4,89% of the total population of Banda Aceh City. Elderly gymnastics is one solution to overcome the problem. On that basis, the D3 Physiotherapy Study Program, Faculty of Vocational University, Muhammadiyah Aceh held Gymnastics with the Elderly. Gampong Keuramat, Kuta Alam District, Banda Aceh City was chosen as a sample for the implementation of these activities. The objectives of holding this Joint Gymnastics for the Elderly are as follows: 1) To improve the physical and spiritual health of the elderly; 2) To make the elderly aware of the importance of elderly exercise in improving health and fitness in the elderly; 3) To increase the sense of community in the elderly; 4) To provide knowledge about the importance of health in the elderly. It is hoped that this elderly exercise will not only be carried out in Keuramat Village but will be carried out in all villages in Banda Aceh City, so that healthy elderly, prosperous elderly, happy people in Banda Aceh City will be created.